By canoe and dog-train among the Cree and Salteaux Indians. - Young, Egerton Ryerson, 1840-1909. (London, C.M. Kelly, 1898)
"Contents" and "List of illustrations" (p. [v]-x) omitted in another edition of same year. Mode of access: Internet.